The Relationship Between Central Obesity and The Incidence of Hypertension in Women of Productive Age in Turirejo Hamlet, Lawang, Malang, Indonesia - dwiaprilawati; Tandry, Muhammad Duffa; Amalia, Agnes; Fahruddin, Ahmad Cholifa; Ramadhan, Akbar Rizky; Fatmadani, Amanah; Sebastian, Pius; Krismaningrum, Veronika Intan; Istianah; Manuela, Grace; Noerlani, Dony (Journal of Community Medicine and Public Health Research, 2024)
Inactivity and sedentary lifestyles, particularly among women who primarily fulfill the role of housewives, are associated with a higher risk of obesity. The 2018 Indonesian Basic Health Research identified a significant prevalence of hypertension among adults aged 55-64, with a disproportionate burden on women. This study aimed to investigate the correlation between obesity and hypertension in women of productive age. This research used descriptive analytics with a cross-sectional design. Data were collected by interviews, blood pressure measurements, and central obesity measurements. The data were collected from Public Health Training Center Murnajati Lawang, Malang, Indonesia. The majority of participants belonged to the 46-55 age group and were non-working individuals. Among the total sample of 50 respondents, 19 (38%) experienced hypertension, with only 3 (6%) exhibiting central obesity. Dietary habits among respondents with central obesity included light to moderate consumption of items such as butter (52%), offal (34%), egg yolks (54%), shrimp (36%), cream milk (54%), mayonnaise (40%), and fatty meats (52%). However, the Fisher test results did not indicate a significant relationship (p= 0.279) between central obesity and hypertension. In conclusion, this study found no evidence of a direct association between central obesity and the incidence of hypertension in women of reproductive age.